2016
DOI: 10.1248/cpb.c16-00001
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Synthesis of Heterocyclic Carboxamide Derivatives as Potent Anti-norovirus Agents

Abstract: There is an urgent need for structurally novel anti-norovirus agents. In this study, we describe the synthesis, anti-norovirus activity, and structure-activity relationship (SAR) of a series of heterocyclic carboxamide derivatives. Heterocyclic carboxamide 1 (50% effective concentration (EC 50 ) 37 µM) was identified by our screening campaign using the cytopathic effect reduction assay. Initial SAR studies suggested the importance of halogen substituents on the heterocyclic scaffold and identified 3,5-di-borom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…5-Bromo-N-(6-fluorobenzo[d]thiazol-2-yl)thiophene-2-carboxamide (BFTC) was synthesized as described previously. 8 For further experiments, theaflavin (TF1), theaflavin-3-O-gallate (TF2A), theaflavin-3′-O-gallate (TF2B) and theaflavin-3, 3′-O, O-digallate (TF3) were purchased from Nagara Science (Gifu, Japan). Tea extracts containing 40% theaflavins and containing 90% theaflavins (obtained by removing caffeine and catechins from the tea extract containing 40% theaflavins) were purchased from Yaizu Suisankagaku Industry (Shizuoka, Japan).…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…5-Bromo-N-(6-fluorobenzo[d]thiazol-2-yl)thiophene-2-carboxamide (BFTC) was synthesized as described previously. 8 For further experiments, theaflavin (TF1), theaflavin-3-O-gallate (TF2A), theaflavin-3′-O-gallate (TF2B) and theaflavin-3, 3′-O, O-digallate (TF3) were purchased from Nagara Science (Gifu, Japan). Tea extracts containing 40% theaflavins and containing 90% theaflavins (obtained by removing caffeine and catechins from the tea extract containing 40% theaflavins) were purchased from Yaizu Suisankagaku Industry (Shizuoka, Japan).…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…Further structural optimization of BFTC resulted in identification of a 70-fold more potent derivative as previously reported. 8 PoSaV-induced CPE was specifically inhibited by EGCG hydrate, abamectin (a mixture of avermectin B1a and B1b) and avermectin B1a (Table 1). EGCG is the most abundant green tea catechin and shows many physiological activities, including antioxidant, antifungal, antibacterial, antiviral, anti-obesity and anti-inflammatory effects.…”
Section: Discovery Of Anti-calicivirus Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…HE chemistry of carboxamide derivatives with various structural moieties have attracted much attention owing to their different biological properties: antimicrobial, [1][2][3][4][5][6] antifungal, [7][8][9][10] anti-inflammatory, [11] analgesic, [12,13] antitumoral, [14][15][16][17][18] antihypertensive, [19,20] anticonvulsant, [21,22] and antiviral [23] in the recent two decades. More than 255 of known drugs have a carboxamide group in its structure.…”
Section: Introductionmentioning
confidence: 99%
“…The bioassay results have shown that some of them exhibited excellent antifungal activities. [23][24][25][26][27][28] It has been proven that pyridine carboxamide group display fungicidal activity by disrupting the mitochondrial tricarboxylic acid cycle (TCA) through inhibition of the succinate dehydrogenase (SDH) enzyme, also called succinate ubiquinone oxidoreductase (SQR). [29] The most of fungicides are heterocyclic toxic substances which selectively destroy fungal phytopatho-gens ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%